Randomization of certain operators in harmonic analysis - Temur, Faruk; Sahillioğulları, Cihan (01. Izmir Institute of Technology, 2024)
Bu tezde, stokastik süreçler aracılığıyla rastsallaştırılmış Hardy-Littlewood majorant problemi çalışılmıştır. Rastsallaştırma için durağan süreçler, rastgele yürüyüşler ve Poisson süreçleri kullanılmış ve bu süreçlerle pertürbe edilmiş deterministik kümeler için Hardy-Littlewood majorant özelliğinin neredeyse kesin olarak geçerli olduğu gösterilmiştir. Poisson süreçleri ile Green-Ruzsa kümesi de dahil olmak üzere çok büyük bir seyrek küme sınıfı pertürbe edilmiştir ve Hardy-Littlewood majorant özelliğinin ihmal edilebilir bir olasılıkla geçerliliğini sürdürdüğü gösterilmiştir. Ayrıca, frekansları daha büyük adım boyutuna sahip bir artimetik ilerleme oluşturan bir üstel toplamın L^2-normu ve L^4-normunun beklenen değerlerinin rastsallaştırmadan nasıl etkilendiği incelenmiştir. Dahası, Poisson süreçleriyle rastsallaştırılmış frekanslara sahip üstel toplamların L^n-normlarının, n ∈ 2N, beklenen değeri kestirilmiş ve bu normlar, ortalama anlamda, bölgeler üzerindeki tam sayı koordinatlı noktalar veya diyofant denklemlerinin çözümleri olarak yorumlanır.

In this thesis, we study Hardy-Littlewood majorant problem randomized via stochastic processes. Stationary processes, random walks and Poisson processes are used for randomization, and we show the Hardy-Littlewood majorant problem holds almost surely for deterministic sets perturbed by these processes. We also perturb a very large class of sparse sets, including the Green-Ruzsa set by Poisson processes and demonstrate that the Hardy-Littlewood majorant property remains valid up to a negligible probability. Additionally, we investigate how randomization affects the expected values of L^2-norm and L^4-norm of an exponential sum whose frequencies constitute an arithmetic progression of larger step size. Furthermore we estimate the expected value of the L^n-norms, n ∈ 2N, of an exponential sums whose frequencies are randomized via Poisson processes, and these norms can be interpreted as lattice points in regions or solutions of diophantine equations in an average sense.
Harmonik analizdeki bazı operatörlerin rastsallaştırılması
Thesis (Doctoral)--İzmir Institute of Technology, Mathematics, Izmir, 2024
Includes bibliographical references (leaves. 129-133).
Text in English; Abstract: Turkish and English
Keywords: Harmonic analysis.; Operator theory